A contabilização de impactos ambientais no setor de papel e celulose: um estudo dos relatórios de sustentabilidade ao relato integrado - Ferreira, Leandro (2017)
The objective of this study was to analyze the financial statements, social reports, sustainability reports and integrated reports from 2014 to 2016 of the companies surveyed, in order to verify if the information contained in these reports is presented in an effective way in relation to the aspects and concepts surveyed, Regarding the theme of environmental impact accounting. The option to restrict the research to companies in the pulp and paper sector listed on the BM&F Bovespa is due to be a reliable source of information. The privately held company International Paper for being one of the largest companies in the industry was also analyzed. The data researched and used to carry out this research were extracted from several bibliographic resources about the subject and the site of the companies object of this study. Finally, it was observed that research organizations have not yet adopted the Integrated Report between the years 2014 and 2016 and that the information on environmental liabilities is not yet clearly evidenced